Cualificación y certificación de la RED LAN con cableado estructurado basado en normas internacionales ANSI /TIA /EIA 568 - B2, en el laboratorio de investigación de Ingeniería de Software, en el año 2017". - Changoluisa Sibitanga, Diego Armando (2017)
In the globalized world of technology nowadays the search to improve communication services and competitiveness is more demanding in the proper management of computer resources. Qualification and certification of a structured cabling under a standard that measures exigency parameters is essential and the objective of the certification is to verify that each wiring point complies with the international operating regulations for maximum working conditions, facilitating the process and sending of data, texts, images, voice, video, multimedia, etc. One of the main problems of a structured cabling network is that it can be connected to the network and can send or receive data does not ensure the quality, speed and availability of the reception process and it is likely that at any time it will start to hinder the entire network. Network, due to a lack of verification and certification. The certification process will first pass through the verification of the network, it is basically the verification of the length, the mapping of the threads and their continuity between ends and allows to confirm that the connection of the cables is actually carried out. Using specific tools such as the Fluke EtherScope Analyzer, which qualifies and certifies a structured cabling system and demonstrates the quality of the components and the installation of the local network, making it easy to check each of the network points and generating Compliance reporting under the ANSI / TIA / EIA 568-B2 standard, which is for a Structured Cabling and local network type management in the Software Engineering Research Lab, will allow for greater performance, availability of efficiency and Efficiency in the operation of the network, which will facilitate teachers and students who will use the laboratory, greater agility, handling of large flows of information without falling packets of data. The certification will allow to verify effectively that the installation has been done correctly and fulfilling all the parameters, for the present as for the future.